TELEVİZYON İMAJI VE SOSYAL GERÇEKLİK - (:unkn) unknown (My University, 2016)
Televizyon gerçekliği ile yaşanılan dünya arasındaki farklar iletişim araştırmalarında önemli bir yer işgal etmektedir. Söz konusu araştırmalar arasında Ekme Kuramı uzun döneme dayalı çalışmaların sonuçlarıyla iletişim alanında ayrıcalıklı bir yerde durmaktadır. Bu çalışmanın konusu da Türkiye'de yayın yapan televizyonlardaki Türkiye ve Türk insanı hakkındaki imajların sosyal hayattakiyle bir karşılaştırılmasına dayanmaktadır. Bu amaçla Türkiye'de yüksek lisans eğitimi yapan yabancı uyruklu öğrencilerle odak grup çalışması gerçekleştirilmiştir. Öğrencilerden televizyon ortamında edindikleri imajlarla, fiziki dünyadaki kendi şahsi gözlemlerinin bir karşılaştırmasını yapmaları istenmiştir. Araştırma için yabancı uyruklu öğrencilerin seçilmesinin nedeni 'dışarıdan gözler' olmaları, bunun yanında ilk kez gördükleri bir ülkeyi anlayabilmek için Türkiye'de yaşayan insanlara göre daha sıkı ve düzenli bir gözlem refleksine sahip olmalarıdır. Öğrencilerin tecrübeleri Ekme Kuramı çerçevesinde yorumlanmaya çalışılmıştır. Buna göre öğrencilerin televizyon deneyimleri ile fiziki dünya gözlemleri arasında büyük farklar bulunmaktadır. Öğrenciler özellikle diziler yoluyla edindikleri kadın erkek ilişkileri ve sosyal etkileşime dair kodların açık toplum imajı verdiği düşüncesindedir. Buna karşılık öğrenciler yaşadıkları fiziki sosyal çevrede etkileşimlerin daha çok mahremiyet üzerinden yürüdüğünü gözlemlemektedirler. Öğrencilerin diğer önemli bir gözlemi televizyon haberleriyle ilgilidir. Buna göre haber bültenlerinde fiziki dünyadaki tecrübelerine ve gözlemlerine kıyasla çok daha fazla şiddet bulunmaktadır. Çalışma sonunda ulaşılan genel bulgular, Ekme Kuramı bağlamında yapılmış, televizyon gerçekliği ile fiziki gerçeklik arasında önemli farklara ulaşan birçok ampirik araştırmayla örtüşmektedir

The differences between television reality and reality of physically experienced world occupy important place in communication researches. Among these researches Cultivation Theory has a distinguished gravity with its long range studies and consequences. The subject of this study depends on comparison of the images about Turkey and Turkish people which spread from Turkish TV channels and the images in social life. For this aim a focus group study has conducted with the foreign master students in Turkey. A comparison asked for students between the images that they obtain from television images and from physical world. The purpose of the choice of foreign students for study is that, they have outsider eyes and they have stronger and regular observe reflex than natives in order to understand a country they came first time. The experiences of the students has examined according to the Cultivation Theory. It is understood that there is a wide gap between the students’ television experiences and their physical observations. Students think that especially the codes at TV series about male – female relations and social interactions give an open society image whereas they observe much more confidentiality in physical life. One of other observations of students is about TV news. According to this observation more violence occurs on news when they compare it with their physical observations. General findings of study are coincided with many empiric studies, which are conducted according to Cultivation Theory that reached the important differences between television reality and physical reality It is so difficult to imagine our homes without television. Television is the most precious household of every modern family. People watches this useful tool in order to have fun, getting information, and to observe the outside world. It opens impressive windows to people. With this features television can be considered as one of the strong sources of the messages. Television is fundamentally different from other forms of mass media. Despite the terrific growth of Internet television is still one of the most consumed communication tool on worldwide. Television creates images to people about the world in which they live. Television shapes the way individuals within society think and relate to each other. Television images can describe way of life, cultures, beliefs and way of evaluation. The effect of television has always been a controversial subject on academic discussions. Television has a central role on changing the norm structures. The extreme images, even the shocking ones, are legitimized by television at public perception. Mediated realities can be related to many different subjects as social relationships, political tendencies, sex issues, economy, religions, sports, social roles etc. The differences between two information sources, television images and real life experiences, are important examination subjects of communication studies. To determine the direction, integrands, and qualification of images spread from television has great important in order to figure out the world of television. For that aim, television images from local to global are under the academicians’ attention. Among these studies Cultivation Theory has a distinguished gravity with its long range studies and consequences. Cultivation Theory suggests that television cultivates to viewers' perceptions of reality. According to theory television viewing can have long-term effects to the audience. The theory also suggests that prolonged watching of television can change the perceptions about violence. Television shapes the social reality with its created images. This study has got its interest from this perspective. What are the differences between the reality which occurred from mediated images and the reality of real life experiences of media consumers? The main subject of this study depends on this main question. The subject of this study depends on comparison of the images about Turkey and Turkish people which spread from Turkish TV channels and the images in social life. For this aim a focus group study has conducted with the foreign master students in Turkey. A comparison asked for students between the images that they obtain from television images and from physical world. The purpose of the choice of foreign students for study is that, they have outsider eyes and they have stronger and regular observe reflex than natives in order to understand a country they saw first time. The experiences of the students have examined according to the Cultivation Theory. The one significant findings of the study is the serials and television news are important sources at the understanding of processes about the culture for foreign students who are newcomers. The other television programs such as documentaries, discussion and competition programs are less viewed television content that foreign students apply to understand the cultural framework. According to students the remarkable images which created at serials are related generally to wealth, life style, and interpersonal relationships. On the other hand the images on television news are generally much related to politics and violence. But both images on serials and television news are not in accordance with the social reality which they observe at physical world. According to students, the images of serials have a spectacle about Turkey that close to European culture rather than Eastern culture. Most of the participators emphasized that they had strong prediction abut Turkey with the features of western life, which depend to the images they get from Turkish channels when they watched at their homeland. Moreover according to foreign students Turkey portrayed in serials with more secular features. Students think that especially the codes at TV series about male – female relations and social interactions give an open society image whereas they observe much more confidentiality in physical life. The other component of television which foreign students think that has no real reflection on physical world is the news. Despite tough policy news, foreign students say that they don’t observe any political interest among their Turkish friends. The other feature which emerges at study is in accordance with the many empiric researches which conducted with the approach of Cultivation Theory. According to foreign students the television messages create interesting images that if one person who watches it would think that Turkish people have strong anger issues. Because of this reason, they don’t want their families to watch Turkish televisions. Foreign students evaluate Turkey and Turkish people not in accordance with the images of television messages that show sharp features. Contrarily according to foreign students Turkey and Turkish people are far from clear conceptualizations as western, eastern, modern, secular, and religious. They think that there is a special unique culture that can be evaluated as “hybrid culture.” There is a wide gap between the definitions about Turkish culture that they reached by their physical world observations and the definitions that depend to the television messages. One of important observations of foreign students about Turkish society on television is the unequal representations of women and people which have low income. They think that in physical world they come across many people from middle and lower classes which have no enough representation on television serials. According to the thoughts of foreign students who use both television images and physical observations in order to understand Turkey and Turkish people, there is a contrast between social reality and television images. Television has its own reality about real life processes. It is understood that there is a significant differences between the students’ television experiences and their physical observations. General findings of the study are coincided with many empiric studies, which are conducted according to Cultivation Theory that reached the important differences between television reality and physical reality.
IMAGE OF TELEVISON AND SOCIAL REALITY